Educational leadership program coordinators : partnership creators through social connectedness - Reames, Ellen H.; Paufler, Noelle A. (Dimensions of leadership and institutional success : exploring connections and partnerships., 2025)
Educational Leadership Program Coordinators: Partnership Creators Through Social Connectedness is an edited volume of chapters which focus on the social bonds and connections formed as program coordinators develop partnerships with K-12 school districts, other higher education institutions, and agencies which support learning in schools and universities. The book is a recent addition to the book series: Dimensions of Leadership and Institutional Success: Exploring Connections and Partnerships, edited by Ellen H. Reames. Ellen and co-editor Noelle A. Paufler created this book to examine the theme of social connectedness and the creative nature of program coordinators. The theme of social connectedness is a key factor in fostering healthy and positive relationships for educational leadership programs and their faculty as they venture into the community at large. The chapters in this volume are laden with the presence of networks established with the community, access to the networks, and a sense of membership and belongingness. These partnerships from a social connectedness lens help assure program stability, resilience, and creativity. This volume examines how program coordinators creatively connect with the larger external and internal environments in what is known as learning partnerships. The editors have included national as well as international treatments of the topic.The primary audience is higher education faculty and administrators. The term program coordinator spans across all disciplines and is used in most higher education institutions across the United States. Higher education institutions are also interested in sustaining partnerships within the university and the communities beyond. This book can assist with nuances of partnership development for any higher education field of study.